The "socialist transformation" of memory : reversing Chinese history through "pernicious-vestiges" media discourse /: reversing Chinese history through "pernicious-vestiges" media discourse. (2023) - Liu, Yusi, 1986-; Ma, Ye, 1989-
No abstract available